Application of Principal Management to Improve Teacher Performance during the Covid 19 Period in Elementary Schools - Mahadin Shaleh; Fauziah Zainuddin; Mukmin Suli (South Sulawesi Education Development (SSED), 2021)
This study aims to: 1) find out the principal management program in improving teacher performance during covid 19 learning at SD Negeri 030 Sabbang Loang, Baebunta District, North Luwu Regency, 2) find out the application of principal management in improving teacher performance during covid 19 at SD Negeri 030 Sabbang Loang, Baebunta District, North Luwu Regency, 3) knowing the results and evaluations faced by teachers during the learning process on covid 19 at SD Negeri 030 Sabbang Loang, Baebunta District, North Luwu Regency. The research method uses a qualitative approach; this type of research uses descriptive research. For data collection, researchers used interviews, documentation, and observation. The results of the problems obtained by researchers are as follows: 1) the principal management program in improving teacher performance during the covid 19 period, the next program carried out by the school is offline to provide convenience to students who do not have technological equipment such as android phones or networks. This program is carried out during the pandemic so that the learning process can continue to run well. The Education Office has created a program during the pandemic to make it easier for students and teachers to carry out the distance learning process. 2) Implementation of principal management in improving teacher performance during covid 19, the management process carried out by school principals through several stages as follows: a) planning b) implementation and c) supervision. 3) Results and evaluations faced by teachers during the learning process in covid 19,